An Integrated Perspective on Virulence-Associated Genes (VAGs), Antimicrobial Resistance (AMR), and Phylogenetic Clusters of Pathogenic and Non-pathogenic Avian Escherichia coli - Seyede Elham Rezatofighi (Frontiers Media S.A., 2021)
Avian pathogenic Escherichia coli (APEC) is an important bacterial pathogen that causes avian colibacillosis and leads to huge economic losses in the poultry industry. Different virulence traits contribute to pathogenesis of APEC infections, and antimicrobial resistance (AMR) has also been an overwhelming issue in poultry worldwide. In the present study, we aimed to investigate and compare the presence of virulence-associated genes (VAGs), AMR, and phylogenetic group's distribution among APEC and avian fecal E. coli (AFEC) strains. E. coli from birds with colisepticemia and yolk sac infection (YSI) (APEC) plus E. coli strains from the feces of healthy birds (AFEC) were compared by the aforementioned traits. In addition, the clonal relatedness was compared using Enterobacterial repetitive intergenic consensus PCR (ERIC-PCR). Although all strains were susceptible to fosfomycin, ceftriaxone, and cefixime, almost all strains (98%) were multi-drug resistant (MDR). All strains (except two) harbored at least three or more VAGs, and the virulence scores tended to be higher in pathogenic strains especially in the colisepticemic group. All phylogenetic groups were found in isolates from YSI, colisepticemia, and the feces of healthy birds; however, the frequency of phylogroups varied according to the source of the isolate. B1 and C phylogroups were statistically more likely to be found among APEC from YSI and colisepticemic E. coli groups, respectively, while phylogroup A was the most frequently occurring phylogroup among AFEC strains. Our findings also revealed that AMR and VAGs are not essentially co-evolved traits as in some instances AMR strains were more prevalent among AFEC. This reflects the divergent evolutionary pathways of resistance acquisition in pathogenic or non-pathogenic avian E. coli strains. Importantly, strains related to phylogenetic group C showed higher virulence score and AMR that requires further attention. To some extent, ERIC-PCR was able to group strains by isolation source, phylogroup, or virulence genes. Further integrated studies along with assessment of more detailed genotypic and phenotypic features could potentially lead to better understanding of virulence, resistance, and evolution of ExPEC.